Measurement of the dynamic charge susceptibility near the charge density wave transition in ErTe 3 - Dipanjan Chaudhuri; Qianni Jiang; Xuefei Guo; Jin Chen; Caitlin S. Kengle; Farzaneh Hoveyda-Marashi; Camille Bernal-Choban; Niels de Vries; Tai-Chang Chiang; Eduardo Fradkin; Ian R. Fisher; Peter Abbamonte (Proceedings of the National Academy of Sciences, 2025)
A charge density wave (CDW) is a phase of matter characterized by a periodic modulation of valence electron density coupled with lattice distortion. Its formation is closely tied to the dynamical charge susceptibility, χ ( q , ω ) , which reflects the collective electron dynamics of the material. Despite decades of study, χ ( q , ω ) near a CDW transition has never been measured at nonzero momentum, q , with meV energy resolution. Here, we investigate the canonical CDW transition in ErTe 3 using momentum-resolved electron energy loss spectroscopy, a technique uniquely sensitive to valence band charge excitations. Unlike phonons, which soften via the Kohn anomaly, we find the electronic excitations exhibit purely relaxational dynamics well described by a diffusive model, with the diffusivity peaking just below the critical temperature, T C 1 . Additionally, we report for the first time a divergence in the real part of χ ( q , ω ) in the static limit ( ω → 0 ), a long-predicted hallmark of CDWs. Unexpectedly, this divergence occurs as T → 0 , with only a weak thermodynamic signature at T = T C 1 . Our study necessitates a reexamination of the traditional description of CDW formation in quantum materials.